The Activin A-Peroxisome Proliferator-Activated Receptor Gamma Axis Contributes to the Transcriptome of GM-CSF-Conditioned Human Macrophages - Nieto, Concha; Bragado, Rafael; Municio, Cristina; Sierra-Filardi, Elena; Alonso, Bárbara; Escribese, María M.; Domínguez-Andrés, Jorge; Ardavín, Carlos; Castrillo, Antonio; Vega, Miguel A.; Puig-Kröger, Amaya; Corbí, Angel L. (Frontiers in Immunology, 2018)
GM-CSF promotes the functional maturation of lung alveolar macrophages, whose differentiation is dependent on the PPARγ transcription factor. In fact, blockade of GM-CSF-initiated signaling or deletion of the PPARγ-encoding gene PPARG leads to functionally defective alveolar macrophages and the onset of pulmonary alveolar proteinosis. In vitro, macrophages generated in the presence of GM-CSF display potent pro-inflammatory, immunogenic and tumor growth-limiting activities. Since GM-CSF upregulates PPARγ expression, we hypothesized that PPARγ might contribute to the gene signature and functional profile of human GM-CSF-conditioned macrophages. To verify this hypothesis, PPARγ expression and activity was assessed in human monocyte-derived macrophages generated in the presence of GM-CSF (pro-inflammatory GM-MØ) or M-CSF (anti-inflammatory M-MØ), as well as in ex vivo isolated human alveolar macrophages. GM-MØ showed higher PPARγ expression than M-MØ, and the expression of PPARγ in GM-MØ was found to largely depend on activin A. Ligand-induced activation of PPARγ also resulted in distinct transcriptional and functional outcomes in GM-MØ and M-MØ. Moreover, and in the absence of exogenous activating ligands, PPARγ knockdown significantly altered the GM-MØ transcriptome, causing a global upregulation of pro-inflammatory genes and significantly modulating the expression of genes involved in cell proliferation and migration. Similar effects were observed in ex vivo isolated human alveolar macrophages, where PPARγ silencing led to enhanced expression of genes coding for growth factors and chemokines and downregulation of cell surface pathogen receptors. Therefore, PPARγ shapes the transcriptome of GM-CSF-dependent human macrophages (in vitro derived GM-MØ and ex vivo isolated alveolar macrophages) in the absence of exogenous activating ligands, and its expression is primarily regulated by activin A. These results suggest that activin A, through enhancement of PPAR expression, help macrophages to switch from a pro-inflammatory to an anti-inflammatory polarization state, thus contributing to limit tissue damage and restore homeostasis.